2014
DOI: 10.1002/jcu.22202
|View full text |Cite
|
Sign up to set email alerts
|

Compression‐refractory breast hematoma secondary to pseudoaneurysm after stereotactically guided vacuum‐assisted biopsy: The critical role of urgent surgical evacuation

Abstract: We report the case of a patient who underwent a vacuum-assisted biopsy of amorphous clustered microcalcifications complicated by a large compression-refractory hematoma secondary to pseudoaneurysm formation. Breast sonography was used to identify an actively bleeding vessel and guide compression. However, due to its unresponsiveness to conventional management and rapid progression, the hematoma required surgical evacuation and ligation of the bleeding vessel. This suggests that, in the face of significant intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Postoperative bleeding is the most common serious complications. It was reported that some cases of bleeding could not be controlled by the standard postprocedural compression following VABB and even required surgical intervention for hemostasis . Apparently, this complication will have a negative effect on patient's recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative bleeding is the most common serious complications. It was reported that some cases of bleeding could not be controlled by the standard postprocedural compression following VABB and even required surgical intervention for hemostasis . Apparently, this complication will have a negative effect on patient's recovery.…”
Section: Discussionmentioning
confidence: 99%
“…14 VABB and even required surgical intervention for hemostasis. 16,17 Apparently, this complication will have a negative effect on patient's recovery. How to prevent postoperative bleeding is still a challenge for the application of VABB.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment can range from manual pressure to surgical ligation. Factors involved in determining the need for definitive intervention include the size of the PA, rate of growth, and need for anticoagulation 1‐7 . Our case describes the first reported successful treatment of a breast PA in an anticoagulated patient.…”
Section: Introductionmentioning
confidence: 91%
“…Needle biopsies can cause several complications including breast bruising, bleeding and hematoma formation [Chou et al 2012]. Controlling an active hemorrhage is a major challenge as a complication of biopsy procedures and therefore clinicians try to take necessary precautions to prevent this complication [Sun et al 2014].…”
Section: Introductionmentioning
confidence: 99%
“…SAds consist of selective serotonergic reuptake inhibitors (SSRIs), serotonin-norepinephrine reuptake inhibitors (SNRIs) and some tricyclic antidepressants (TCAs) with high affinity to serotonin receptors [Mahdanian et al biopsies can cause several complications including breast bruising, bleeding and hematoma formation [Chou et al 2012]. Controlling an active hemorrhage is a major challenge as a complication of biopsy procedures and therefore clinicians try to take necessary precautions to prevent this complication [Sun et al 2014].…”
Section: Introductionmentioning
confidence: 99%